Factors Associated with Cocoa Farmers' Participation in the Training and Visit Extension System in the District of Jerantut, State of Pahang, Malaysia - Sulong, Abdul Manaf (1986)
The main purpose of this study was to determine factors affecting participation of the cocoa farmers in the programmes of the Training and Visit System (T&V) in the District of Jerantut. The specific objective was to determine the relationship between the level of participation in the T&V Programmes with factors such as demographic, situational, personal and attitudes as well as perception of the importance and relevance of the T&V Programmes. The respondents of the study were cocoa farmers registered under the T&V System in the District of Jerantut and 113 of them were selected as samples for the study. The data collected were analysed using the Statistical Package For Social Science subprogrammes including frequencies, reliability, correlation, anova and regression. The study revealed that the level of participation, the level of perception of importance and relevancy of the T&V were generally high. Several factors were found to be positively related to the level of participation of cocoa farmers in the T&V Programmes, namely: 1) demographic factors (number of years of education completed, level of cash income and farm size); 2) situational factors (level of cosmopoliteness, initiative of extension agents, political affiliations and number of positions held in non-political (achievement organizations); 3) orientation, efficacy personality in public traits affairs orientation toward planning and optimism); 4) attitudes (attitude towards the T&V System, change agents and change agencies, modernization, and voluntary organisations); and 5) perception (perception of importance and relevance of the T&V Programmes). Based on the regression analysis involving all variables utilized in the study, the variable achievement orientation was found to have the highest explanatory power in explaining the variance in participation, followed by perception of relevance and importance of the T&V Programmes, efficacy in public affairs, political affiliations, positions held in the farmers' group of the T&V System, and initiative of extension agents. Based on the findings of the study, seven recommendations to improve farmers' participation in the T&V extension programmes were presented. In addition, eight problem areas that need further research were also forwarded.